The Dynamic of Calcium Oxalate (CaOx) in Porang Corms (Amorphophallus muelleri Blume) at Different Harvest Time - Chairiyah, Nurul; Harijati, Nunung; Mastuti, Retno (Journal of Tropical Life Science, 2021)
The research aims to observe the influence of harvesting time on the change of calcium oxalate (CaOx) content and crystal density in Porang corms. The corms were harvested at different times, i.e., (1) two weeks before the plants shed (R0-1), (2) when the plants shed (R0), and (3) two weeks after the plants shed (R0+1). CaOx was obtained using the modified extracting method. Microscopic observations were obtained from the slices of the edge and center part of porang corms. Parameter observed including CaOx content, corm weight, shape, and density of CaOx crystal. CaOx content and crystal density in corms were analyzed using One way ANOVA. If the results are significant, it will be followed by Tukey Test α 0.05. In the meantime, the relation between CaOx content and corm weight was analyzed using Correlation Test Bivariate. The results showed that CaOx content was relatively higher in porang corms, i.e., 15.98 ± 0.60g/100g. On the other hand, the increasing of CaOx content might improve corm weight. The total density of druse, styloid, and prism crystal was pretty high in corms obtained when the plants shed compared to another harvest time, i.e., 1,494 ± 286; 31,280 ± 17,406 and 6,256 ± 1,533 crystals/cm2 . Raphide crystal density, by contrast, increased in corms obtained after the plants shed, i.e.,1,656 ± 368 crystals/cm2 . Total CaOx crystal density in the edge parts of corms harvested when the plants shed was proportionately higher than in the other harvest times, i.e., 12,292 ± 4,687.89 crystals/cm2 . In contrast, CaOx crystal densities in the center parts of corms were not much different at three harvesting times. The density of druse and prism crystals was somewhat higher in the center part of corms than in the edge parts. In opposition to, the density of raphide and styloid crystals was fairly higher in the edge part of corms than it was in the center parts. However, only raphide crystal density found in the edge and center part of corms was significantly affected by harvest time from all these results.